2015
DOI: 10.1111/den.12570
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate‐risk patients with three to four small adenomas should be considered low risk for colorectal cancer screening

Abstract: Intermediate-risk patients with three to four small adenomas achieved a very low advanced lesion rate at follow up. Surveillance interval should be lengthened because these patients should be considered low risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…23 A cohort study of 561 individuals with 3-4 adenomas <10 mm suggested that the risk for metachronous advanced neoplasia among individuals with 3-4 adenomas was <5%. 33 This study was limited by the absence of a comparison group with only 1-2 nonadvanced adenomas. In a cohort study of 443 individuals with 1-9 adenomas <10 mm, no group with <10-mm polyps (including those with between 5 and 9 adenomas) had a rate of metachronous advanced neoplasia >10% on follow-up that extended up to 32 months.…”
Section: Recommended Post-colonoscopy Surveillance Strategies For Reducing Colorectal Cancer Riskmentioning
confidence: 99%
“…23 A cohort study of 561 individuals with 3-4 adenomas <10 mm suggested that the risk for metachronous advanced neoplasia among individuals with 3-4 adenomas was <5%. 33 This study was limited by the absence of a comparison group with only 1-2 nonadvanced adenomas. In a cohort study of 443 individuals with 1-9 adenomas <10 mm, no group with <10-mm polyps (including those with between 5 and 9 adenomas) had a rate of metachronous advanced neoplasia >10% on follow-up that extended up to 32 months.…”
Section: Recommended Post-colonoscopy Surveillance Strategies For Reducing Colorectal Cancer Riskmentioning
confidence: 99%
“…Patients who had both ACRN and ASP were classified into the ACRN group. Patients were also classified into four groups according to the total number of colon polyps: 1–2, 3–4, 5–9, and 10 or more, referring to previous studies [ 6 , 7 ]. Non-neoplastic polyps, such as inflammatory polyps, were not considered in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Although initial follow-ups were rather narrow 4 , in recent years, there has been a trend toward widen surveillance intervals 5 . Recent data show that some patients considered by the European guidelines for quality assurance in CRC 6 to be at high risk of advanced neoplasia during surveillance have the same outcomes as those at intermediate risk 7 and that some patients considered to be at intermediate risk may have outcomes similar to those at low risk 8 . The recently published European Society of Gastrointestinal Endoscopy (ESGE) guidelines address this new evidence and recommend not performing endoscopic surveillance in patients with complete excision of up to four adenomas < 10 mm regardless of the presence of a villous component.…”
Section: Introductionmentioning
confidence: 99%